Honey bees as biomonitors of environmental contaminants, pathogens, and climate change. (January 2022) - Cunningham, Morgan M.; Tran, Lan; McKee, Chloe G.; Ortega Polo, Rodrigo; Newman, Tara; Lansing, Lance; Griffiths, Jonathan S.; Bilodeau, Guillaume J.; Rott, Michael; Marta Guarna, M.
Graphical abstract: Highlights: Environmental monitoring is crucial for protecting human and ecosystem health. Honey bees ( Apis mellifera ) can serve as global, continuous biomonitoring species. Colonies are resilient and accumulate or respond to stressors without collapsing. Long-range foragers transport pollutants, pesticides, and pathogens to their hives. A. mellifera may serve to monitor emerging threats such as climate change and AMR. Abstract: Monitoring the environment for pollution, pesticides, and pathogens is crucial for protecting human, agriculture, and overall ecosystem health. Diverse strategies ranging from physical sensors to sentinel species have been used for environmental monitoring. The European honey bee, Apis mellifera, is a globally managed pollinator that can serve as a continuous biomonitoring species. During foraging, honey bees are exposed to contaminants and pathogens and carry them to their hives where they can be detected and quantified. Although individual bees are vulnerable to environmental stressors, the honey bee colony as a whole is more resilient and can accumulate contaminants or respond to them without collapsing. This allows for long-term monitoring of the colony to map contaminants in a geographical area and study ecotoxicology gradients over space and time. In this paper, we review demonstrated and proposed uses of honey bees for environmental monitoring. We focus our discussion on heavy metals, air pollutants, pesticides, and plant pathogens that can be detected in bees and their hive materials including honey, wax, and stored pollen. We present the use of gene expression, microbiome profiling, and other high-throughput methodologies to study dose-dependent exposure and increase detection sensitivity; for example, stored pollen analysis with next generation sequencing can reveal the presence of plant viruses, fungi, and invasive species earlier than traditional detection methods. Finally, we discuss opportunities for using honey bees to monitor emerging threats such as climate change and antimicrobial resistance. This narrative review highlights the versatility and potential utility of the European honey bee as a biomonitoring species for ecosystem health.